2005
DOI: 10.1080/15421400590930782
|View full text |Cite
|
Sign up to set email alerts
|

Lasing Thresholds of Cholesteric Liquid Crystals Lasers

Abstract: Cholesteric liquid crystals (CLCs) are one dimensional photonic band-gap materials. Due to distributed feedback, low threshold mirrorless lasing can occur in dye-doped and pure CLCs. In order to optimize the lasing conditions, we have studied the dependence of the lasing threshold on dye concentration and sample thickness. In particular, we have studied dye concentrations in the range of 0.1-3.0wt%, and cell thicknesses are in the range of 5-50µm. We have found that the system has a shallow lasing threshold mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…8. This is in accordance with previous studies, where optimization of the dye concentration has been shown to increase the emission intensities [29][30][31] and reduce the threshold energies 28,30 of N ‫ء‬ LC lasers. The most striking feature is that the efficiencies of the PM597 lasers were always higher than those of the two other laser samples, irrespective of dye concentration.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…8. This is in accordance with previous studies, where optimization of the dye concentration has been shown to increase the emission intensities [29][30][31] and reduce the threshold energies 28,30 of N ‫ء‬ LC lasers. The most striking feature is that the efficiencies of the PM597 lasers were always higher than those of the two other laser samples, irrespective of dye concentration.…”
Section: Discussionsupporting
confidence: 81%
“…It is important to mention that Cao et al 28 also studied the lasing thresholds of DCM-doped N ‫ء‬ LC laser samples, using a chiral nematic liquid crystalline host ͑BLO61, EM industries͒ diluted with a nematic ͑E7, EM industries͒. The range of dye concentrations used here corresponds to their intermediate concentration regime ͑0.25-2.5 wt % DCM͒, where they found that E th increased linearly with increasing DCM concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al studied the lasing thresholds of cholesteric liquid crystal lasers as a function of dye concentration and of sample thickness [33]. Figure 3 shows the threshold dependence on dye concentration.…”
Section: Lasing In Dye Doped Cholesteric Liquid Crystalmentioning
confidence: 99%
“…Considering the size of the p-c cavity (microwell diameter is approximately 40 µm. ), the lasing threshold in terms of total pump energy is approximately 0.73 nJ, whereas existing band-edge lasers exhibit lasing thresholds a few orders of magnitude higher [12,17,23,24]. For comparison between the p-c and p-p cavities, spectrally integrated lasing intensities from a part of the LC-filled sandwich cell without the microwell are also measured.…”
Section: Resultsmentioning
confidence: 99%